Advancement in the Fluid Dynamics Research of Reversible Pump-Turbine - Tao, Ran; Ye, Changliang; Song, Xijie (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pumped storage technology is a large-scale, efficient, flexible and clean energy storage technology. The core of it is the design of pumped storage units, which involves the operation and flow characteristics of vane hydraulic machinery under pump and turbine modes, as well as the complex flow conditions of the upstream and downstream flow channels of the units. With this as the background, this book expounds on the relevant problems and their solutions, providing a scientific basis for the development of pumped storage technology. I hope this book can provide as a useful reference for readers.